The impact on non-traditional security threats in Sri Lanka - Ong, Jessica Hai Liaw; Nadeeka de Silva,; Nora Ibrahim,; Abdul Hamid Moiden,; Munira Abdul Razak,; Adlina Abd Khalil, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The security threats exert a great challenge to national security of all states irrespective of the state’s position in the international system. In the field of security studies, with the transition of state-centric security to individual security approach, non-traditional security issues have become a novel concept of security studies. As a maritime nation Sri Lanka’s strategic location in the centre of the Indian Ocean makes it visible, perhaps vulnerable, to many external and internal threats. Hence, the government has to take immediate steps to mitigate these non-traditional security threats in order to ensure the national security and economic prosperity. This article is to examine the security environment and perspective of national security in Sri Lanka, identify the non-traditional security threats and analyse the impact on national security and identify mitigation methods to ensure national security. Methodology used were the primary and secondary data of a qualitative research method by using ethnographic study. Findings for this study is Sri Lanka must shape the security environment through an effective and realistic assessment of national interest. A great priority is to be given for the political stability while maintaining the continuous vigilance, to seek active cooperation and coordination effort within the region and beyond and engage in continuous process of confidence building within the nation and beyond. The findings of this study are the model-based approach is a better solution for Sri Lanka to overcome these security challenges, however, application of any model should be tailored to Sri Lanka’s own specifications.